2016
DOI: 10.1002/jcb.25610
|View full text |Cite
|
Sign up to set email alerts
|

Canine Adipose‐Derived Stem Cells: Purinergic Characterization and Neurogenic Potential for Therapeutic Applications

Abstract: The presented results evidence that canine adipose-derived stem cells (ADSCs) represent the premature population of stem cells with great biological potential and properties. ADCS are easy to obtain and culture, able to differentiate into the neurogenic lineage as well as it is easy to control their proliferation rate with nucleotides and nucleosides or analogues. We report that in vitro cultured canine ADSCs response to adenosine- and ATP-mediated stimulation. Differences in canine ADSCs and human mesenchymal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 41 publications
5
14
0
Order By: Relevance
“…The stimulatory role of Ado in the proliferation of murine and human MSCs due to the A2A receptors activation is well documented (Katebi et al, ; Riddle et al, ). Consistently, similar results were also obtained for canine MSCs isolated from the adipose tissue (Roszek et al, ). It seems that, independently from the tissue of origin, the undifferentiated MSCs are characterized by high proliferative and regenerative potential additionally increased by Ado supplemented into the extracellular environment.…”
Section: Purinergic Signaling System In Mscssupporting
confidence: 86%
“…The stimulatory role of Ado in the proliferation of murine and human MSCs due to the A2A receptors activation is well documented (Katebi et al, ; Riddle et al, ). Consistently, similar results were also obtained for canine MSCs isolated from the adipose tissue (Roszek et al, ). It seems that, independently from the tissue of origin, the undifferentiated MSCs are characterized by high proliferative and regenerative potential additionally increased by Ado supplemented into the extracellular environment.…”
Section: Purinergic Signaling System In Mscssupporting
confidence: 86%
“…Moreover, we postulate that during differentiation, cells become more sensitive to ATP‐mediated signaling, which is often related to cell stress or damage. It was previously observed that MSCs are resistant to the cytotoxic effect induced by ATP [Ferrari et al, ; Roszek et al, ]. Here we present that ATP increases neurogenic transdifferentiation efficiency.…”
Section: Discussionsupporting
confidence: 71%
“…GFAP, MAP2, A2B5, S100, TUBB3, nestin, and NEUN are markers of neural cells and can be used as markers of cellular differentiation in vitro. Canine adipose tissue-derived multipotent mesenchymal stromal cells (ASCs) could be induced to express some of these neuronal genes after growing in the presence of the neurogenic inductors valproic acid and forskolin [14,16], basic fibroblast growth factor (bFGF), and epidermal growth factor (EGF) [15], in a commercial neurogenic differentiation medium [18] and in a medium containing N2 supplement, brain-derived neurotrophic factor (BDNF), and nerve growth factor (NGF) [19]. Neurospheres generated from the canine ASCs were used to enrich for neural lineages sufficiently expanded to transplant [19] and, when grown in hypoxia, showed higher expression of the neuronal marker nestin [20].…”
Section: Introductionmentioning
confidence: 99%